Alzheimer's Disease and Anesthesia - Papon, Marie-Amélie; Whittington, Robert A.; El Khoury, Noura; Planel, Emmanuel (Frontiers in Neuroscience, 2011)
Cognitive disorders such as post-operative cognitive dysfunction, confusion, and delirium, are common following anesthesia in the elderly, with symptoms persisting for months or years in some patients. Alzheimer's disease (AD) patients appear to be particularly at risk of cognitive deterioration following anesthesia, and some studies suggest that exposure to anesthetics may increase the risk of AD. Here, we review the literature linking anesthesia to AD, with a focus on the biochemical consequences of anesthetic exposure on AD pathogenic pathways.